Beyond the Game: Perceptions and Practices of Corporate Social Responsibility in the Professional Sport Industry - Sheth, Hela (Journal of business ethics, 2010)
Corporate social responsibility (CSR) is an area of great interest, yet little is known about how CSR is perceived and practiced in the professional sport industry. This study employs a mixed-methods approach, including a survey, and a qualitative content analysis of responses to open-ended questions, to explore how professional sport executives define CSR, and what priorities teams have regarding their CSR activities. Findings from this study indicate that sport executives placed different emphases on elements of CSR including a focus on philanthropic activities and ethical behaviors. The data suggest that professional sport executives view CSR as a strategic imperative for their business. Sport executives indicated that a number of factors influenced the practice of their CSR including: philanthropy (altruistic giving), an emphasis on the local community, partnerships, and ethical concerns. We also examine important organizational variables for sport (winning, revenues, and team value) and highlight their relationship with reported CSR involvement. We discuss the implications of the findings and propose recommendations for both theory and practice.